Synthesis of pd-tb/c and pd-tb2o3/c electro-catalysts for ethanol oxidation in alkaline media - Tan, Delphine Si Ling. (2010)
To date, most energy needs are provided by the combustion of fossil fuels. However, fossil fuels are not sustainable, especially so when the limited reserves deplete significantly in the face of increasing energy demand. This motivates the development of alternative technologies such as the fuel cell technology for efficient energy conversion and power generation. Direct ethanol fuel cells (DEFCs) are clean and efficient energy conversion devices. However, commercialization of DEFCs is hindered by the use of Pt, an expensive metal, in the electrocatalysts of DEFCs. Also, the use of acid media in DEFCs leads to severe corrosion. Hence, the possibility of Pd-based electrocatalysts for ethanol oxidation reaction (EOR) in alkaline DEFCs is explored. In this project, Pd-Tb/C electrocatalysts were synthesized by a reduction method with NaBH4. Pd-Tb2O3 rod/C and Pd-Tb2O3 cube/C electrocatalysts were synthesized by a hydrothermal and calcination method with sodium hydroxide in addition to a reduction method using NaBH4. X-Ray diffraction was used to characterize the structure of the catalysts. Electrochemical tests namely cyclic voltammetry, linear sweep voltammetry and chronoamperometry techniques were used to characterize the catalysts’ electrocatalytic activities for EOR in alkaline media. Among the Pd-Tb/C catalysts, 10%Pd-2%Tb/C exhibits superior catalytic activity for ethanol oxidation in alkaline media. Pd-Tb2O3 cube/C has higher activity and stability as compared to Pd-Tb2O3 rod/C.